Unmasking the 'pro bodoh' mindset: escaping the nerakazen trap - Roslan, Muhammad Azril (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Malaysia was recently shaken by a tragic school-related death in Sabah, but rather than revisiting the incident, this piece highlights the alarming legal ignorance displayed by many netizens. The issue is not just a lack of knowledge, but the confidence with which misinformation is spread online. A bit of reading before posting would prevent careless comments, as what people write reveals their understanding and whether they are thoughtful or simply loud and uninformed.